Synthesis and Characterisation of Zirconium Complexes for Cell Tracking with Zr-89 by Positron Emission Tomography - Ferris, Trevor J (Dalton Trans, 2014)
The increasing availability of the long half-life positron emitter Zr-89 (half life 78.4 h) suggests that it is a strong candidate for cell labelling and hence cell tracking using positron emission tomography. The aim was to produce a range of neutral ZrL(4) lipophilic complexes for cell labelling which could be prepared under radiopharmaceutical conditions. This was achieved when the ligand was oxine, tropolone or ethyl maltol. The complexes can be prepared in high yield from zirconium(IV) precursors in hydrochloric or oxalic acid solution. The oxinate and tropolonate complexes were the most amenable to chromatographic characterisation, and HPLC and ITLC protocols have been established to monitor their radiochemical purity. The radiochemical synthesis and quality control of (89)Zr(oxinate)(4) is reported as well as preliminary cell labelling data for the oxinate, tropolonate and ethyl maltolate complexes which indicates that (89)Zr(oxinate)(4) is the most promising candidate for further evaluation.